2018
DOI: 10.1021/acs.inorgchem.8b01038
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Synthesis, Crystal and Electronic Structures, and Optical and Thermoelectric Properties of Sr1–xSbxHfSe3 Orthorhombic Perovskite

Abstract: Single-phase polycrystalline powders of SrSb HfSe ( x = 0, 0.005, 0.01), a new member of the chalcogenide perovskites, were synthesized using a combination of high temperature solid-state reaction and mechanical alloying approaches. Structural analysis using single-crystal as well as powder X-ray diffraction revealed that the synthesized materials are isostructural with SrZrSe, crystallizing in the orthorhombic space group Pnma (#62) with lattice parameters a = 8.901(2) Å; b = 3.943(1) Å; c = 14.480(3) Å; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 86 publications
(96 reference statements)
0
28
0
Order By: Relevance
“…Different crystalline structures were observed, depending on the [Ba]/([Sr] + [Ba]) ratio: NH 4 CdCl 3 type for 0 < x < 0.68 values, biphasic mixtures of NH 4 CdCl 3 and CsNiCl 3 ‐type compounds for 0.68 < x < 1.0 values, and commensurate mismatched chain compound for the Ba 1.07 ZrSe 3 having a new orthorhombic needle‐like structure. Recently, Moroz et al have reported the synthesis of Sr 1–x Sb x HfSe 3 crystals having a needle‐like (orthorhombic) SrZrSe 3 type structure, using a combination of mechanical alloying and solid‐state reaction at elevated temperature (800 °C) methods. The doping of the SrHfSe 3 compound with Sb led to the increase of the bandgap (from 1.05 eV for x = 0 to 1.15 eV for x = 0.1).…”
Section: Experimental Studies: Synthesis Methods For Oxy‐chalcogenidesmentioning
confidence: 99%
“…Different crystalline structures were observed, depending on the [Ba]/([Sr] + [Ba]) ratio: NH 4 CdCl 3 type for 0 < x < 0.68 values, biphasic mixtures of NH 4 CdCl 3 and CsNiCl 3 ‐type compounds for 0.68 < x < 1.0 values, and commensurate mismatched chain compound for the Ba 1.07 ZrSe 3 having a new orthorhombic needle‐like structure. Recently, Moroz et al have reported the synthesis of Sr 1–x Sb x HfSe 3 crystals having a needle‐like (orthorhombic) SrZrSe 3 type structure, using a combination of mechanical alloying and solid‐state reaction at elevated temperature (800 °C) methods. The doping of the SrHfSe 3 compound with Sb led to the increase of the bandgap (from 1.05 eV for x = 0 to 1.15 eV for x = 0.1).…”
Section: Experimental Studies: Synthesis Methods For Oxy‐chalcogenidesmentioning
confidence: 99%
“…ABSe 3 compounds with slightly smaller A cations, namely, SrZrSe 3 , [ 74 ] SrHfSe 3 , [ 82 ] and EuZrSe 3 , [ 94 ] were all grown in the NH 4 CdCl 3 ‐type phase. To the best of our knowledge, no phase transitions or alternative crystal structures have been reported for these compounds, in contrast to their sulfide relatives.…”
Section: The Discovered Chalcogenide Perovskitesmentioning
confidence: 99%
“…−1 . [ 121 ] ) From the experimental side, the synthesis was carried out at temperatures of 800 °C or higher, [ 74,82 ] and hence the difference in the entropy contribution to free energy must have been significant. This factor is ignored in standard energy calculations dealing with ground states (T = 0 K).…”
Section: The Discovered Chalcogenide Perovskitesmentioning
confidence: 99%
“…Meng et al [31] studied the BaZr1-xTixS3 alloy system, suggesting a limited concentration range before phase separation takes place. Optical and thermoelectric properties of SrHfSe3 and Sr1-xSbxHfSe3 were also studied [32]. Intense green luminescence characteristics were found in both undoped and heavily n-and p-doped SrHfS3 [28].…”
Section: Introductionmentioning
confidence: 99%